European Union-28: An annualised cost-of-illness model for venous thromboembolism - Barco, Stefano; Woersching, Alex L.; Spyropoulos, Alex C.; Piovella, Franco; Mahan, Charles E. (Thrombosis and Haemostasis, 2016)
Annual costs for venous thromboembolism (VTE) have been defined within the United States (US) demonstrating a large opportunity for cost savings. Costs for the European Union-28 (EU-28) have never been defined. A literature search was conducted to evaluate EU-28 cost sources. Median costs were defined for each cost input and costs were inflated to 2014 Euros (€) in the study country and adjusted for Purchasing Power Parity between EU countries. Adjusted costs were used to populate previously published cost-models based on adult incidence-based events. In the base model, annual expenditures for total, hospital-associated, preventable, and indirect costs were €1.5–2.2 billion, €1.0–1.5 billion, €0.5–1.1 billion and €0.2–0.3 billion, respectively (indirect costs: 12 % of expenditures). In the long-term attack rate model, total, hospital-associated, preventable, and indirect costs were €1.8–3.3 billion, €1.2–2.4 billion, €0.6–1.8 billion and €0.2–0.7 billion (indirect costs: 13 % of expenditures). In the multiway sensitivity analysis, annual expenditures for total, hospital-associated, preventable, and indirect costs were €3.0–8.5 billion, €2.2–6.2 billion, €1.1–4.6 billion and €0.5–1.4 billion (indirect costs: 22 % of expenditures). When the value of a premature life-lost increased slightly, aggregate costs rose considerably since these costs are higher than the direct medical costs. When evaluating the models aggregately for costs, the results suggests total, hospital-associated, preventable, and indirect costs ranging from €1.5–13.2 billion, €1.0–9.7 billion, €0.5–7.3 billion and €0.2–6.1 billion, respectively. Our study demonstrates that VTE costs have a large financial impact upon the EU-28’s healthcare systems and that significant savings could be realised if better preventive measures are applied.
Keywords: Venous thromboembolism; annual costs; European Union; preventable costs; thromboprophylaxis